The Effect of a Program of Fundamental Football Skill Training on the Cognitive Performance of Novice Iraqi Football Players with the Moderating Role of Age - Alsarki , Mokdad Bashir Hussein; Serjuei, Zahra; Alsarkhi , Mohammed Hussein Hameedi; Zahedi , Hamid (Mental Health and Lifestyle Journal, 2026)
The purpose of the present study was to examine the effect of a program of fundamental football skill training on the cognitive performance of boys aged 9 to 12 years. The research design was quasi-experimental using a pretest–posttest format with a control group. The statistical population consisted of male elementary school students and football academy trainees in the city of Maysan, Iraq. From this population, 60 participants were purposively selected and assigned to four groups: three experimental groups aged 9–10, 10–11, and 11–12 years (15 participants in each group) who participated in the training protocol, and one control group (15 participants) that received no intervention. The mean age of the control group was 10.6 years, which was positioned in the mid-range of the experimental age groups. The training protocol lasted eight weeks with three sessions per week and focused on fundamental football skills including dribbling, passing, shooting, coordination, and small-sided games. The research instruments included Raven’s Progressive Matrices test for the assessment of cognitive performance. Data were analyzed using analysis of covariance (ANCOVA) and the Bonferroni post-hoc test. The results indicated that fundamental football skill training had a statistically significant effect on cognitive performance (F = 12.84, p < .001, η² = .27). In addition, interaction effects demonstrated the moderating role of age, such that children aged 11–12 years exhibited the greatest improvement compared with the younger groups, whereas the control group showed only minimal changes from pretest to posttest. Overall, the findings indicate that fundamental football skill training enhances cognitive performance. These results highlight the importance of designing and implementing structured physical activity programs in schools and extracurricular activities and may serve as an effective model for the holistic development of children during the sensitive developmental period of 9 to 12 years of age.